The Dynamics of an Electric Vehicle-Based Mobility Sharing Economy in Densely Populated Cities - Amelia Hayati (Nomico, 2025)
Urban population growth in developing countries has intensified challenges in urban mobility, including traffic congestion, rising transportation costs, and worsening air pollution. Electric vehicle (EV)-based sharing mobility emerges as a promising alternative by combining the principles of the sharing economy with clean transportation solutions. This study aims to analyze the economic dynamics of EV-sharing in densely populated cities, focusing on cost efficiency, emissions reduction, local economic opportunities, and operational challenges. A qualitative descriptive approach was employed, combining systematic literature review of 2019–2025 scholarly works, institutional reports, and policy documents, complemented by case comparisons from Asia and Africa. Data were analyzed thematically and validated through triangulation across multiple sources. Findings indicate that EV-sharing reduces per-kilometer travel costs by lowering energy and maintenance expenses, while simultaneously cutting carbon emissions and improving urban air quality. Moreover, the system fosters local economic opportunities through new jobs in charging infrastructure, fleet management, and battery services, as demonstrated by cases such as Yulu in India and Oyika in Southeast Asia. Nonetheless, challenges persist, particularly limited charging infrastructure, grid instability, high initial investment, regulatory weaknesses, and socio-cultural adoption barriers. Overall, EV-sharing represents not only a sustainable transportation solution but also a catalyst for economic transformation in the clean energy transition era of developing cities.